1998
DOI: 10.1002/lt.500040511
|View full text |Cite
|
Sign up to set email alerts
|

Parental psychosocial outcomes in pediatric liver and/or intestinal transplantation: Pretransplantation and the early postoperative period

Abstract: Although liver transplantation has become an effective treatment for end-stage liver disease and liver/intestine transplantation is becoming an increasingly viable procedure for end-stage shortgut syndrome in children, little is known about the impact of these procedures on the child's family. Examination of the impact of these transplantations on the family is needed to identify psychosocial factors that may adversely affect the child's physical and emotional health and to plan for preventive interventions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 31 publications
4
38
0
2
Order By: Relevance
“…These findings are in keeping with previously reported higher rates of depression, anxiety, and symptoms of posttraumatic stress disorder (PTSD) among parents of children either listed for LT and in parents of children who have undergone LT [2224]. It is important to note that parental stress has been associated with impaired clinical outcomes after LT, including poor adherence to treatment and poor health outcomes [20].…”
Section: Discussionsupporting
confidence: 86%
“…These findings are in keeping with previously reported higher rates of depression, anxiety, and symptoms of posttraumatic stress disorder (PTSD) among parents of children either listed for LT and in parents of children who have undergone LT [2224]. It is important to note that parental stress has been associated with impaired clinical outcomes after LT, including poor adherence to treatment and poor health outcomes [20].…”
Section: Discussionsupporting
confidence: 86%
“…We also found that patients missed on average 7-9 days of school or work/year for physician visits and hospitalizations. Other studies of QOL in this patient group are limited to a small number of adult recipients and to an assessment of the QOL of the parent (12)(13)(14)(15). No previous studies of QOL of pediatric intestinal transplant recipients using validated instruments were identified in the literature, although children account for a large proportion of intestinal transplant recipients.…”
Section: Introductionmentioning
confidence: 99%
“…Although parenting stress was not elevated compared with a normative sample, having a younger child going through transplantation was associated with higher stress. Parents reported better physical function but lower vitality than the normative population [173].…”
Section: Quality Of Life In Small Bowel Transplantmentioning
confidence: 99%